2009
DOI: 10.1085/jgp.200910290
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of ClC-1 and KATP channels in action potential–firing fast-twitch muscle fibers

Abstract: Action potential (AP) excitation requires a transient dominance of depolarizing membrane currents over the repolarizing membrane currents that stabilize the resting membrane potential. Such stabilizing currents, in turn, depend on passive membrane conductance (Gm), which in skeletal muscle fibers covers membrane conductances for K+ (GK) and Cl− (GCl). Myotonic disorders and studies with metabolically poisoned muscle have revealed capacities of GK and GCl to inversely interfere with muscle excitability. However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
100
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(106 citation statements)
references
References 38 publications
(47 reference statements)
6
100
0
Order By: Relevance
“…9, 10 After blocking muscle contraction with BTS, 5000 action potentials were delivered at 20 Hz in skeletal muscle from ClC adr mice using a protocol similar to one that has been used on wild type skeletal muscle fibers. 11, 12 We examined whether prolonged firing of action potentials led to resolution of myotonia. Myotonia was classified as the continued firing of action potentials following the end of a 60 ms depolarizing pulse.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…9, 10 After blocking muscle contraction with BTS, 5000 action potentials were delivered at 20 Hz in skeletal muscle from ClC adr mice using a protocol similar to one that has been used on wild type skeletal muscle fibers. 11, 12 We examined whether prolonged firing of action potentials led to resolution of myotonia. Myotonia was classified as the continued firing of action potentials following the end of a 60 ms depolarizing pulse.…”
Section: Resultsmentioning
confidence: 99%
“…31 In wild type rat muscle, it was found that prolonged firing of action potentials triggered a marked increase in membrane conductance. 11, 12 While it appeared that most of the increase in conductance was mediated by ClC-1 choride channels, there was also increased potassium conductance. 11, 12 To measure changes in resting membrane conductance, a 60ms hyperpolarizing pulse was given to measure input resistance.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This fits with the clinical observation that in patients with transient weakness, warm-up causes increased strength-quite the opposite of fatigue. Interestingly, investigations into the mechanisms of muscle fatigue by Pedersen et al [47,48] showed that normal muscle can alter its membrane conductances on a time scale of seconds during trains of action potentials. Perhaps this type of phenomenon could be involved in warm-up of myotonic muscle.…”
Section: Clcn1 and Myotonia Congenitamentioning
confidence: 99%